ANALYSIS OF STUDENTS' CONCEPTUAL UNDERSTANDING AND THE CAUSES OF THEIR MISKONCEPTIONS USING THE FIVE-TIER MULTIPLE CHOICE TEST ON STATIC FLUID - Carnesia, Mita; Mufit, Fatni (Universitas Negeri Padang, 2024)
Misconception is a misunderstanding of the notion of learning material that can result in a mismatch between the conceptions held by someone and scientific concepts or concepts owned by scientists. Misconception can impede learning progress. The purpose of this study is to assess students' concept knowledge and misperception profile, as well as to identify the reasons of students' misconceptions about static fluid.The data was collected using a five-tier multiple choice test instrument with 14 items and five-level multiple choice questions. The respondents or samples in this study were 213 students from three different schools, categorized as low, middle, and high. This study used a purposive sampling strategy.Overall, the results showed the highest concept understanding in the material of the main law of hydrostatics, namely 54 students, in the category of understanding the concept partly in the material of viscosity, namely 128 students, the highest misconceptions experienced by students in the material of Archimedes' law concept as many as 144 students and the category did not understand the highest concept in the material of the main law of hydrostatics, namely 37 students. Concept understanding is in the low category in each school, the highest partial concept understanding is in high category schools followed by low category schools and medium category schools, the highest misconceptions occur in low category schools, not understanding the concept is in the low category in each school. The main cause of misconceptions is students' personal thinking.